AB1094 Leucine-Rich-Alpha Glycoprotein-1 (LRG1) and Lupus Nephritis. (9th June 2015) - Ohkawara, T.; Lee, H.; Serada, S.; Hosono, Y.; Fujimoto, M.; Mimori, T.; Naka, T.
Abstract : Background: Systemic Lupus erythematousis (SLE), which pathology is not well understood, is an autoimmune disorder with a range of presentations. Among these, lupus nephritis (LN) is a particularly severe feature of SLE that predicts a poor outcome. 1 Classification of lupus nephritis is determined by renal biopsy, whitch is a very invasive diagnostic method. Objectives: To develop a new noninvasive diagnostic method to classify lupus nephritis, we focused on urinary level of Leucine-rich alpha-2-glycoprotein-1 (LRG1), which is a novel inflammatory maker and expressed at inflammation in the inflammatory local site. 2 Methods: We divided SLE patients into four groups (group 1: LN class 1 and 2 (ISN/RPS), group 2: LN class 3 and 4, group 3: LN class 5 and group 4: unknown), and compared serum and urinary level of LRG1 between groups by ELISA. Next, using a spontaneous animal lupus nephritis model NZB/NZW F1 mouse, we evaluated the expression of LRG1 in kidney by real-time PCR, Immunohistochemistry (IHC), in situ hybridization, and measured serum and urinary level of LRG1 by ELISA. Results: In SLE patients, group 2 was the highest in the urinary level of LRG1 and, group 1 and group 3 was slightly higher than healthy control. In NZB/W F1 mouse, urinary LRG1 was detected at 5 or 6months old, and gradually elevated. In 8 months old mouse exhibiting LN class 2–4, expression of LRG1 was observed in renal tubular epithelial cells in IHC and in situ hybridization, in realtime PCR, we comfirmed that LRG1 expression was elevated in kidney. Conclusions: Measuring urinary level of LRG1 can become a new maker of LN. LRG1 may be involved in the pathogenesis of LN. References: Golbus J, McCune WJ. Lupus nephritis. Classification, prognosis, immunopathogenesis, and treatment. Rheumatic diseases clinics of North America 1994;20(1):213-42. Serada S, Fujimoto M, Terabe F, et al. Serum leucine-rich alpha-2 glycoprotein is a disease activity biomarker in ulcerative colitis. Inflammatory bowel diseases 2012;18(11):2169-79. Disclosure of Interest: None declared